(untitled) (The Review of Diabetic Studies, 2024)
Introduction: Medication safety is one of the key issues of the Saudi Arabian health care system, especially in the context of the Kingdom, which is rapidly transforming on the levels of digitization and structure in the context of Saudi Vision 2030. Medication errors (MEs) are a major challenge to patient care and hospital expenditures. Being the key professionals that provide the ultimate part of the drug administration process, nurses are the key gatekeepers that assure patient safety. Nevertheless, due to the versatile characteristics of their work, which are neutralized by both high workloads and a multinational working environment, there are unique challenges that need to be systematically researched. Study Objective: This study’s objective is to examine and evaluate the numerous ways that nurses have had an influence on prevention, identification, and communication of medication errors in Saudi Arabian hospital settings as well as the effect on all areas of safety in relation to drug administration in Saudi Arabia. Methodology: The systematic review was carried out in line with the PRISMA guidelines. A detailed search was conducted in databases such as PubMed, CINAHL, Google Scholar, and the Saudi Medical Journal on articles published during the last 2-6 years. The search employed the Boolean operators to connect the keywords like Nursing, Medication Safety, and Saudi Arabia. Thematic analysis method was used to extract and synthesize data and the quality of the studies was appraised in order to guarantee the soundness of the results. Conclusion: The results have shown that even though nurses make it very effective to intercept the error before it reaches the patients, the work is often undermined by the systemic factors, such as high patient-to-nurse rates and fear-induced reporting culture. Accuracy has increased due to the use of technological tools such as Barcoded Medication Administration (BCMA) but human factor is the most important variable. The research comes to a conclusion that to meet its patient safety objectives, Saudi Arabia needs to move towards a shift between punitive and a Just Culture, as well as to increase pharmacological education and streamline the nursing processes so that mental strain and disruptions take place.